Crafting Experience: The Role of Sensory and Emotional Design in E-Learning Narratives - Roy Anthonius Susanto; Christian Orvin Widodo (Universitas Multimedia Nusantara, 2026)
While digital storytelling tools increasingly incorporate sensory and emotional design elements, the effectiveness of these elements in an experiential learning environment remains less clear and needs to be explored further. This research enhances the investigation of this topic through a qualitative multiple case study of three platforms: Gentlerain.ai, The Blue Desert, and Expo 58 Virtual Pavilion. These platforms were chosen for their story-driven e-learning features and emphasis on narrative frameworks. Data were produced by conducting a series of methodical UI/UX walk throughs and observing the primary platforms. Each instance was evaluated based on a framework that included narrative composition, sensory details, emotional connection, interaction design, consistency with Kolb’s experiential learning cycle, and management of cognitive load. The findings indicate that visual design serves as a primarly elements but not yet standardized across platforms. While it serves as a medium to direct attention, emotional and argumentative burdens can sometimes reduce the engagement effectiveness. Tactile interactivity, in contrast, was not strongly associated with affective engagement; for example, The Blue Desert evoked emotional responses despite minimal tactile interaction. Cross-case comparisons further illustrate that narrative structure is fundamental for sustaining overall engagement with design attention and impact, thereby influencing the learning outcomes achievable through Kolb’s experiential learning cycle. This research presents the Narrative Sensory Experiential Learning Model along with a design checklist for designers. This contribution is framed not only in relation to the model itself but also concerning the cross-case process that demonstrates the value of qualitative and structured analysis of digital platforms.